Optimasi Isolasi Protoplas Mesofil Daun Anggrek Paraphalaenopsis laycockii - UTAMI, EDY SETITI WIDA; HARIYANTO, SUCIPTO (Agrotrop : Journal on Agriculture Science, 2016)
Optimalization protoplast isolation of the leaves mesophyll orchid Paraphalaenopsis layockii. The obyectives of the research was to investigate the effect of combination treatment of sucrose concentrations and incubation time on protoplast isolation of the leaves mesophyll orchid of Paraphalaenopsis layockii. The factorial experiment consisted of two factors that was arranged by completely randomized design (CRD) with ten replications. The first factor was concentrations of sucrose which consists of three levels namely 0.4 M, 0.5 M and 0.6 M. The second factor was incubation time which consists of four levels namely 2 hours, 4 hours, 6 hours and 8 hours. Data were analyzed using Kruskal-Wallis test followed by Mann-Whitney test. The results showed that there was effect of treatment for all variables observed. The highest protoplast density and number of viable protoplasts achieved in the combined treatment of 0.6 M sucrose and 4 hours of incubation time.
Keywords: protoplast isolation; leaves mesophyll; Paraphalaenopsis layockii